Legitimasi Agama Terhadap Perlawanan Rasisme: Analisis Film Pengepungan di Bukit Duri Perspektif Emile Durkheim - Taufikurrohman , Taufikurrohman; Yaqin, Haqqul (UIR Press, 2025)
This study aims to examine in depth how religion functions as a source of moral and social legitimacy in confronting and resisting racism as depicted in Joko Anwar’s film The Siege at Bukit Duri. The film was chosen because it portrays complex social dynamics where religion operates not only as a belief system but also as a moral foundation that strengthens solidarity amid social tension and identity conflict. This research employs a qualitative method with a content analysis design to interpret the symbolic meanings of scenes that portray discrimination, injustice, and the community’s resistance against social and political hegemony. Émile Durkheim’s theory serves as the main framework to explain religion’s role as a social fact that shapes collective consciousness, maintains moral order, and reinforces human values. The findings show that religious symbols such as the hijab, religious figures, and the slogan “we are all the same” act as forms of moral legitimacy that strengthen solidarity against discrimination. The urgency of this research lies in its contribution to expanding the sociology of religion through popular media, which reflects contemporary social realities and demonstrates how religious values can become a means of resistance to domination.